Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
y = 2x+5
y = 6x+1
Just substitute.
y = 2x+5
6x+1 = 2x+5
6x-2x = 5-1
4x = 4
x = 1
Then, insert x = 1 into one of the equation. Let's say I choose number one.
y = 2x+5
y = 2(1) + 5
y = 7
y = 6x+1
Just substitute.
y = 2x+5
6x+1 = 2x+5
6x-2x = 5-1
4x = 4
x = 1
Then, insert x = 1 into one of the equation. Let's say I choose number one.
y = 2x+5
y = 2(1) + 5
y = 7
y=2x+5
y=6x+1
y=2x+5
2x+5=6x+1
y=2x+5
2x-6x=1-5
y=2x+5
-4x=-4 / : (-4)
y=2x+5
x=1
x=1
y=2*1+5
x=1
y=2+5
x=1
y=7
y=6x+1
y=2x+5
2x+5=6x+1
y=2x+5
2x-6x=1-5
y=2x+5
-4x=-4 / : (-4)
y=2x+5
x=1
x=1
y=2*1+5
x=1
y=2+5
x=1
y=7
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.